Pengaruh Intensitas Modal dan Pertumbuhan Penjualan Terhadap Tax Avoidance Dengan Kepemilikan Institusional Sebagai Pemoderasi - Bunga Safitri; Rudy (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to examine the partial and simultaneous effects of Capital Intensity and Sales Growth on Tax Avoidance in energy sector companies listed on the Indonesia Stock Exchange (IDX). This quantitative research utilizes secondary data from annual financial statements and annual reports of energy sector companies during 2019–2023. The population consists of 90 companies listed on the IDX in the specified period. Using purposive sampling, a sample of 16 companies was selected. Hypotheses were tested using multiple linear regression analysis assisted by Eviews version 12. The results indicate that Capital Intensity and Sales Growth simultaneously influence Tax Avoidance. However, Capital Intensity does not have a significant effect on Tax Avoidance, whereas Sales Growth has a significant positive effect. Furthermore, Institutional Ownership does not moderate the relationship between Capital Intensity and Tax Avoidance, but it does moderate the relationship between Sales Growth and Tax Avoidance.